The Impact of Ambiguity Prudence on Insurance and Prevention - Loïc Berger (Fondazione Eni Enrico Mattei (FEEM), 2015)
Most decisions concerning (self-)insurance and self-protection have to be taken in situations in which a) the effort exerted precedes the moment uncertainty realises, and b) the probabilities of future states of the world are not perfectly known. By integrating these two characteristics in a simple theoretical framework, this paper derives plausible conditions under which ambiguity aversion raises the demand for (self-)insurance and self-protection. In particular, it is shown that in most usual situations where the level of ambiguity does not increase with the level of effort, a simple condition of ambiguity prudence known as decreasing absolute ambiguity aversion (DAAA) is sufficient to give a clear and positive answer to the question: Does ambiguity aversion raise the optimal level of effort?
Keywords: D61; D81; D91; G11; 330; Non-expected Utility; Self-protection; Self-insurance; Ambiguity Prudence